Long way home; The life history of Chinese-Indonesian migrants in the Netherlands - Kitamura, Yumi (UI Scholars Hub, 2017)
The purpose of this paper is to trace the modern history of Indonesia through the experience of two Chinese Indonesians who migrated to the Netherlands at different periods of time. These life stories represent both post-colonial experiences and the Cold War politics in Indonesia. The migration of Chinese Indonesians since the beginning of the twentieth century has had long history, however, most of the previous literature has focused on the experiences of the